The Effectiveness of Android-Based Audio-Visual Media in Enhancing Quran Memorization Skills of Students at Taman Pendidikan al-Quran, Kurir Langit Modern Islamic Boarding School, Barru Regency - Aziziyah Alam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The aim of using audio-visual media is to develop cognitive abilities by providing stimuli in the form of moving images and sound, and to convey messages that influence attitudes and emotions. This study examines the implementation and effectiveness of using Android-based audio-visual media to improve students' Quran memorization skills. The research method used is descriptive qualitative, with field research as the type of study. Primary data were obtained from direct interviews with ustadz, ustadzah, and students at the boarding school, while secondary data were collected from books, journals, and articles related to the topic. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The results of this research are as follows: (1) The implementation of audio-visual media shows that educators have applied Android-based audio-visual media for students at Kurir Langit Modern Islamic Boarding School, Barru Regency. This media helps ustadz/ustadzah deliver Quran memorization methods more effectively and attracts the students' attention. (2) The effectiveness of using Android-based audio-visual media indicates that it has been effective in enhancing the memorization skills of the students. However, some students prefer memorizing the Quran without audio-visual aids due to difficulties in understanding the technology.